Loss to Follow-Up After Pregnancy Among Sub-Saharan Africa-Born Women Living With Human Immunodeficiency Virus in England, Wales and Northern Ireland: Results From a Large National Cohort - Tariq, Shema (Sex Transm Dis, 2016)
BACKGROUND: Little is known about retention in human immunodeficiency virus (HIV) care in HIV-positive women after pregnancy in the United Kingdom. We explored the association between loss to follow-up (LTFU) in the year after pregnancy, maternal place of birth and duration of UK residence, in HIV-positive women in England, Wales, and Northern Ireland. METHODS: We analyzed combined data from 2 national data sets: the National Study of HIV in Pregnancy and Childhood; and the Survey of Prevalent HIV Infections Diagnosed, including pregnancies in 2000 to 2009 in women with diagnosed HIV. Logistic regression models were fitted with robust standard errors to estimate adjusted odds ratios (AOR). RESULTS: Overall, 902 of 7211 (12.5%) women did not access HIV care in the year after pregnancy. Factors associated with LTFU included younger age, last CD4 in pregnancy of 350 cells/μL or greater and detectable HIV viral load at the end of pregnancy (all P < 0.001). On multivariable analysis, LTFU was more likely in sub-Saharan Africa-born (SSA-born) women than white UK-born women (AOR, 2.17; 95% confidence interval, 1.50–3.14; P < 0.001). The SSA-born women who had migrated to the UK during pregnancy were 3 times more likely than white UK-born women to be lost to follow-up (AOR, 3.19; 95% confidence interval, 1.94–3.23; P < 0.001). CONCLUSIONS: One in 8 HIV-positive women in England, Wales, and Northern Ireland did not return for HIV care in the year after pregnancy, with SSA-born women, especially those who migrated to the United Kingdom during pregnancy, at increased risk. Although emigration is a possible explanatory factor, disengagement from care may also play a role.